2006
DOI: 10.1038/sj.clpt.6100046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in the ABCB1 Gene and the Effects of Fentanyl in Koreans

Abstract: P-glycoprotein (PGP) is a polymorphic transporter encoded by the ABCB1 gene that contributes to the access of xenobiotics into the brain. There is no report on associations between genetic polymorphisms in ABCB1 and the clinical effects of fentanyl, although fentanyl may be a substrate of PGP. One hundred and twenty-six (126) unrelated Korean patients under spinal anesthesia with intravenous fentanyl (2.5 microg/kg) were recruited. Clinical effects (bispectral index, respiration rate, and need for oxygen suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…Based on the patient genotypes of the SNPs listed above, Campa et al (2007) were able to predict patients as being 'strong responders', 'responder' or 'nonresponders' with sensitivity close to 100% and specificity more than 70%. In addition to the aforementioned 3435C4T ABCB1 alleles, 1236C4T and 2677G4T/A protect against the respiratory depressive effects of fentanyl (Park et al, 2006).…”
Section: See Also: Opiates and Opioidsmentioning
confidence: 99%
“…Based on the patient genotypes of the SNPs listed above, Campa et al (2007) were able to predict patients as being 'strong responders', 'responder' or 'nonresponders' with sensitivity close to 100% and specificity more than 70%. In addition to the aforementioned 3435C4T ABCB1 alleles, 1236C4T and 2677G4T/A protect against the respiratory depressive effects of fentanyl (Park et al, 2006).…”
Section: See Also: Opiates and Opioidsmentioning
confidence: 99%
“…Some genetic variants of the ABCB1 and ABCG2 genes are believed to influence the pharmacokinetics of their substrates, as reported for the opiates methadone (2) and fentanyl (3), which are putative P-gp substrates, whose distributions may be influenced by P-gp activity (4). Regional variations in the function of P-gp at the BBB of individuals with neurologic disorders such as epilepsia, Parkinson disease, and Alzheimer disease (1,5) may occur.…”
mentioning
confidence: 99%
“…A number of in vivo studies have concluded that fentanyl is a P-gp substrate while one suggested it is rather an Oatp substrate (136). Clinical results are not in consensus either, with some suggesting P-gp function has a significant role in the pharmacodynamics of fentanyl (131,132), while others suggest otherwise (133,134). Clinical evidence also suggests fentanyl is not an OATP substrate, implying fentanyl may be safely concomitantly administered with OATP substrates or inhibitors (135).…”
Section: Fentanylmentioning
confidence: 95%
“…Another clinical study of 126 patients undergoing spinal anesthesia found certain ABCB1 genotypes were linked with increased fentanyl-induced respiratory depression. Patients with the genotypes 1236TT, 2677TT, and 3435TT were found to have early and profound respiratory depression (65-73% of initial respiratory rate) following intravenous fentanyl administration, suggesting ABCB1 polymorphisms may have important clinical implications in fentanyl safety (132). However, another clinical study of 83 patients also undergoing intravenous fentanyl treatment for spinal anesthesia concluded that ABCB1 polymorphisms had no effect on fentanyl-induced sedation or respiratory depression (133).…”
Section: Fentanylmentioning
confidence: 96%
See 1 more Smart Citation